Successful Flexible Bronchoscopic Management of Dynamic Central Airway Obstruction by a Large Tracheal Carcinoid Tumor - Vijay Hadda; Karan Madan; Anant Mohan; Umasankar Kalai; Randeep Guleria (Case Reports in Pulmonology)
Typical carcinoid of the trachea presenting as an endoluminal polypoidal mass is a rare occurrence. Herein, we report a case of a 34-year-old female patient who presented with features of central airway obstruction. Flexible bronchoscopy demonstrated a large pedunculated growth arising from the lower end of the trachea near carina which was flopping in and out of the main tracheal lumen and the proximal right bronchus leading to dynamic airway obstruction. Successful electrosurgical excision (using a snare loop) of the polypoidal growth was performed using the flexible bronchoscope itself. The patient had immediate relief of airway obstruction and histopathological examination of the polyp demonstrated features of typical carcinoid (WHO Grade I neuroendocrine tumor).